Standardized generation of fully mature p70 IL-12 secreting monocyte-derived dendritic cells for clinical use - Špíšek, Radek; Bretaudeau, Laurent; Barbieux, Isabelle; Meflah, Khaled; Gregoire, Marc (Cancer immunology and immunotherapy, 2001)
Dendritic cells (DC) have been shown to be efficient antigen-presenting cells (APC) and, as such, could be considered ideal candidates for cancer immunotherapy. Immature DC (iDC) efficiently capture surrounding antigens; however, only mature DC (mDC) prime naive T lymphocytes. Clinical trials using DC-based tumor vaccines have achieved encouraging, but limited, success, possibly due to the use of immature or incompletely mature DC. Thus, it was apparent that a method capable of generating large numbers of fully functional iDC, their pulsing with desired form of tumor antigens and the subsequent complete and reproducible maturation of iDC is needed. Therefore, we compared two different methods of producing large numbers of iDC. Both protocols yielded comparable numbers of cells with an iDC phenotype with phagocytic function. We next determined which of the clinically applicable activators could induce the complete and reproducible maturation of DC, in order to define the most suitable combination for future clinical trials. Only a combination of TNFalpha + Poly (I:C), or a previously described cytokine cocktail of TNFalpha + IL-1beta + IL-6 + prostaglandin E2, induced the complete activation of the whole DC population, as assessed by the cell surface expression of CD83 and costimulatory molecules. The matured DC were functionally superior to iDC in their ability to stimulate the proliferation of allogeneic lymphocytes and autologous keyhole limpet hemocyanin (KLH)-specific T lymphocytes. Furthermore, only the combination of TNFalpha + Poly (L:C) activated DC to produce large amounts of biologically active p70 IL-12. Thus DC maturation by TNFalpha + Poly (I:C) could efficiently bias T cell response towards Th1 response. Implementation of our results into clinical protocols used for DC generation could be beneficial for future immunotherapy trials.
Keywords: Apoptosis; nádorové buňky kultivované; Cell Survival; Immunophenotyping; kultivované buňky; Cells, Cultured; melanom; Recombinant Proteins; Phagocytosis; Interleukin-6; Interleukin-13; terciární struktura proteinů; Hemocyanins; dendritické buňky; lidé; buněčná diferenciace; rekombinantní proteiny; Reproducibility of Results; Tumor Cells, Cultured; buněčné dělení; Cell Culture Techniques; reprodukovatelnost výsledků; interleukin-12; interleukin-13; Poly I-C; viabilita buněk; dinoproston; apoptóza; Dendritic Cells; faktor stimulující granulocyto-makrofágové kolonie; Interleukin-12; Lymphocyte Culture Test, Mixed; Humans; TNF-alfa; Protein Structure, Tertiary; Cell Differentiation; hemokyanin; poly I-C; Dinoprostone; Flow Cytometry; imunofenotypizace; interleukin-6; buněčné kultury; Cell Division; Granulocyte-Macrophage Colony-Stimulating Factor; průtoková cytometrie; test smíšené lymfocytární kultury; fagocytóza; Interleukin-1; Melanoma; Tumor Necrosis Factor-alpha; interleukin-1